NORMATIVE SELECTIVITY ON THE RUNWAY: THE FRENCH “ANTI-FAST FASHION” LAW, CONSUMER RIGHTS, AND THE STRUCTURAL OMISSION OF HAUTE COUTURE AS AN ENVIRONMENTAL ISSUE: A LEI FRANCESA “ANTI FAST FASHION”, O DIREITO DO CONSUMIDOR E A OMISSÃO ESTRUTURAL DA ALTA-COSTURA COMO PROBLEMA AMBIENTAL (ESMAT Magazine, 2026)
This article examines the fashion industry, highlighting its social, cultural, and environmental dimensions, marked by rapid consumption and disposability. The focus lies on the French “anti-fast fashion” legislation, which imposes disclosure duties, advertising restrictions, and environmental fees on ultra-fast fashion platforms such as Shein and Temu. The research problem investigates whether the law effectively protects the environment or, by centering on consumption, shifts responsibility onto lower-income consumers while neglecting the systemic impacts of haute couture. The hypothesis maintains that, although symbolically significant, the regulation is selective and partial. The objective is to critically assess the law in light of Consumer Law and Environmental Law. The method adopted is analytical-deductive, based on a bibliographic review of relevant literature concerning fashion and its intersections with Environmental and Consumer Law, and, specifically, of the recent French legislation on fast fashion. The article is structured in two parts: the first examines the environmental impacts of fashion associated with ultra-fast production and France’s new regulation; the second addresses the contradictions of haute couture. The conclusion is that, although the legislation represents progress in addressing fast fashion, it remains structurally limited: it acts on symptoms, while haute couture and its externalities, including carbon footprint and controversial practices, remain largely untouched, thereby revealing regulatory inequality and accountability gaps.
Keywords: Haute couture; Consumption; Fast fashion; Fashion industry; Environment